060. Chronic Megacolon with Recto Vaginal Fistulo Associated with Atresia Ani: A 26-Year History and Case Report - Arditayasa, I Gede Ryan; Antara, Gede Eka Rusdi (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical Education, 2024)
Background : Large bowel obstruction and megacolon formation with rectovaginal fistule ascociated with atresia ani is rare. abnormal colon dilatation that falls into one of three categories: toxic, chronic, or acute. Acute megacolon, sometimes called Ogilvie syndrome, is a condition that frequently affects sick or postoperative individuals and is linked to autonomic nervous system dysfunction. Its source is unknown. On the other hand, intestinal dysfunction brought on by neurological or muscle conditions is the cause of chronic megacolon. The symptoms of all three kinds include bloating, stomach pain, and constipation. Case : We present a case of an 26-year-old woman surviving large bowel obstruction and mega-megacolon formation secondary atresia ani and fistulo rectovagina for 26years alive, with an presentation of abdominal distention. Results The patient’s symptoms, laboratory test results, and imaging were consistent with large bowel obstruction. The patient underwent urgent exploratory laparotomy. Upon entry in the abdomen, it was unexpected that the extreme colonic wall thickening, indicating the longtime course of illness. In this instance, we performed a number of procedures, including ligation of the obstructed colon, anus repair, and vaginal fistula repair. Conclusion: This report aims to point out the atypical and in-extremes presentation of an otherwise common disease.